2004
DOI: 10.1039/b212259f
|View full text |Cite
|
Sign up to set email alerts
|

β-Phenylethylamines and the isoquinoline alkaloids

Abstract: This review covers beta-phenylethylamines and isoquinoline alkaloids derived from them, including further products of oxidation. condensation with formaldehyde and rearrangement, some of which do not contain an isoquinoline system, together with naphthylisoquinoline alkaloids, which have a different biogenetic origin. The occurrence of the alkaloids, with the structures of new bases, together with their reactions, syntheses and biological activities are reported. The literature from July 2002 to June 2003 is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(21 citation statements)
references
References 445 publications
0
21
0
Order By: Relevance
“…However, Lautens et al 20 reported that rhodium-catalysed ring opening of 1,4-dihydroepoxyquinoline failed to react by using [Rh(COD)Cl] 2 with or without DPPF or protic additives such as NH 4 Cl. In contrast, they successfully performed rhodium-catalysed ring opening of 1,4-dihydroepoxyquinoline by a catalyst prepared by simply combining Rh(COD) 2 OTf and (R,S)-PPF-P(t-Bu) 2 in THF at 60 °C. Consequently, [Rh(COD)Cl] 2 can be used for ring opening reactions of azaoxabicyclic compounds instead of Rh(COD) 2 OTf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lautens et al 20 reported that rhodium-catalysed ring opening of 1,4-dihydroepoxyquinoline failed to react by using [Rh(COD)Cl] 2 with or without DPPF or protic additives such as NH 4 Cl. In contrast, they successfully performed rhodium-catalysed ring opening of 1,4-dihydroepoxyquinoline by a catalyst prepared by simply combining Rh(COD) 2 OTf and (R,S)-PPF-P(t-Bu) 2 in THF at 60 °C. Consequently, [Rh(COD)Cl] 2 can be used for ring opening reactions of azaoxabicyclic compounds instead of Rh(COD) 2 OTf.…”
Section: Resultsmentioning
confidence: 99%
“…[Rh(COD)Cl] 2 can also be used as catalyst in the ring opening reactions of azaoxabicyclic compounds instead of Rh(COD) 2 OTf. This report describes an effective and concise strategy for a new flexible synthesis of dihydroisoquinoline derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16] Recently, we synthesized a more activated THF model, 1-tosyl-3,4-dimethylimidazolinium iodide (1). [13][14][15][16] Recently, we synthesized a more activated THF model, 1-tosyl-3,4-dimethylimidazolinium iodide (1).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The isolation and synthesis of naturally occurring tetrahydro-β-carboline derivatives and the synthesis of tetrahydro-β-carboline derivatives have received considerable attention in the literature. 1,2 The isolation and synthesis of naturally occurring tetrahydro-β-carboline derivatives and the synthesis of tetrahydro-β-carboline derivatives have received considerable attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the most promising are those involving diverse and readily available starting materials, as they enable wide variation of the pharmacophore environment. As a vivid example, the long-known Pictet-Spengler reaction [1-3] may be mentioned (Scheme 1); it is extensively applied for synthesis of the tetrahydro-b-carboline ring system occurring in many natural and synthetic compounds and providing diverse biological activity [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%